Evolving Trends in Surgical Management of Breast Cancer: An Analysis of 30 Years of Practice Changing Papers - Keelan, Stephen; Flanagan, Michael; Hill, Arnold D. K. (Frontiers in Oncology, 2021)
The management of breast cancer has evolved into a multidisciplinary evidence-based surgical speciality, with emphasis on conservative surgery. A number of landmark trials have established lumpectomy followed by radiation as the standard of care for many patients. However there has been a shift towards mastectomy for early-stage breast cancer in recent years. The aim of this study is to construct a narrative review of recent developments in the surgical management of breast cancer and how such developments have impacted surgical practice. A comprehensive literature search of Pubmed was conducted. The latest search was performed on October 31st, 2020. Search terms “breast cancer” were used in combinations with specific key words and Boolean operators relating to surgical management. The reference lists of retrieved articles were further screened comprehensively for additional eligible publications. Articles were selected and reviewed based on relevance. We selected publications in the past 10 years but did not exclude commonly referenced and highly regarded previous publications. Review articles and book chapters were also cited to provide reference on details not discussed in the academic literature. This article reviews the current evidence in surgical management of early-stage breast cancer, discusses recent trends in surgical practice for therapeutic and prophylactic procedures and provides commentary on implications and factors associated with these trends.